2016
DOI: 10.5751/ace-00876-110204
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving territory size and breeding success in a threatened migratory songbird, the Canada Warbler

Abstract: ABSTRACT. Successful conservation of migratory birds demands we understand how habitat factors on the breeding grounds influences breeding success. Multiple factors are known to directly influence breeding success in territorial songbirds. For example, greater food availability and fewer predators can have direct effects on breeding success. However, many of these same habitat factors can also result in higher conspecific density that may ultimately reduce breeding success through density dependence. In this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Land use practices that support retention or recruitment of dense shrubby understory could further enhance the conservation value of managed forests for Canada Warblers. However, a recent study in Alberta found that the Canada Warbler has smaller territories and lower fecundity in areas with high shrub cover, possibly because of increased resource competition (Flockhart et al 2016). Further research is needed to determine whether early seral habitats function as reproductive sources or sinks in western boreal forests, some of which is ongoing (A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land use practices that support retention or recruitment of dense shrubby understory could further enhance the conservation value of managed forests for Canada Warblers. However, a recent study in Alberta found that the Canada Warbler has smaller territories and lower fecundity in areas with high shrub cover, possibly because of increased resource competition (Flockhart et al 2016). Further research is needed to determine whether early seral habitats function as reproductive sources or sinks in western boreal forests, some of which is ongoing (A.…”
Section: Discussionmentioning
confidence: 99%
“…Hard and soft vegetated linear features were never the dominant land cover and were dropped from the list of local-scale land cover categories. We modeled their effect based on a dummy variable for the presence of a road in the 150-m buffer (i.e., roadside surveys) and the proportion of vegetated linear features, because it is known that their presence can introduce biases when not accounted for (Marques et al 2010, Bayne et al 2016. We also accounted for biases related to survey methodology.…”
Section: Biophysical Attributesmentioning
confidence: 99%
“…) to avoid potential density‐dependent nest predation (Mitchell & Brown ; Flockhart et al . ). We did not use flagging tape to mark artificial nests (Yahner & Wright ).…”
Section: Methodsmentioning
confidence: 97%
“…Canada Warblers nest on the forest floor, where high stem densities conceal nests and improve reproductive success (Goodnow and Reitsma 2011), while supporting higher Canada Warbler abundances (Hobson and Bayne 2000). Additionally, Canada Warblers that arrive earlier on their breeding grounds choose sites with greater understory stem density (Hallworth et al 2008b), and territory size decreases with increasing shrub density (Flockhart et al 2016).…”
mentioning
confidence: 99%